The Legalization of Photography of Canadian Prisoners - Stacy, Sarah (Archivaria, 2008)
This article documents the origins of the use of photography within federal penitentiaries in Canada. Drawing primarily on correspondence from the Department of Justice records at Library and Archives Canada, and using examples from the Kingston Penitentiary Inmate History Description Ledgers, the Canadian experience and social response is compared with contemporary developments in the United States, England, and France. Whether federal legislation may have af fected police practices at the municipal level is also discussed. RÉSUMÉ Ce texte trace les origines de l’usage de la photographie dans les pénitenciers fédéraux au Canada. En se servant principalement de la correspondance tirée du fonds du ministère de la Justice, conservé à Bibliothèque et Archives Canada, et en utilisant des exemples tirés des registres des détenus du pénitencier de Kingston (« Kingston Penitentiary Inmate History Description Ledgers »), l’expérience et la réaction sociale canadiennes sont comparées aux expériences contemporaines des États-Unis, de l’Angleterre et de la France. L ’auteure examine aussi le rôle qu’a pu jouer la législation fédérale sur les pratiques policières au niveau municipal.